PEMBELAJARAN CD-ONLINE BAGI GURU-GURU YAYASAN BERNARDUS DI KOTA SEMARANG - Ratna Kusumawardhani; Th. Cicik Sophia Budiman; Entika Fani Prastikawati (Universitas PGRI Semarang, 2011)
Abstract: This community service is carried out in form of trainingin making teaching and learning media in the form of CD-O (CDOnline)for teachers of Theresiana Junior High School 1 inSemarang. It was held on Saturday, August 6th 2011 in Laboratory ofTheresiana Junior High School 1 and Sunday, August 7th 2011 inIKIP PGRI Semarang laboratory. There were 20 teachers ofTheresiana Junior High School 1 which were taken part in thiscommunity service. The purpose of this community service is thatteachers are able to make blog and learning materials through CDOnline.It is expected that they can create an innovative learningmaterial. The methods used were explaining, questioning andanswering, and practicing making blog and CD-Online.Key words: Blog, CD-Online, Learning materials.